Marketing and trade policies for genetically modified products: Lessons from South Africa - Gruère, Guillaume P.; Sengupta, Debdatta (International Food Policy Research Institute, 2009)
This brief analyzes the past successes and recent challenges of South Africa’s trade and marketing policies on genetically modified (GM) products, with the aim of drawing lessons for countries that are designing their biosafety systems.